Exploring student anxiety when starting in a joint international Master's programme. Issue 7 (9th August 2021) - Jung, Julia; Jahnke, Isa; Deprez, Tim
ABSTRACT: There are a handful of programmes in higher education that offer students a joint international study programme and research shows that students have certain levels of anxiety when starting studying in such graduate programmes. This study aimed to explore levels of student anxiety and investigates the prerequisite skills in order to better prepare students for studying in an international Master programme of Marine Biological Resources with 10 European campuses in seven countries. We applied mixed-methods including online questionnaires and interviews capturing student experiences and teachers' perspectives. Results show that especially mature and non-native English-speaking students experience anxiety and that there is a high class-heterogeneity in terms of academic background and life experience. This may simultaneously act as a barrier for and enable learning. The presented results show a need to improve the student acculturation process in international programmes. This could be done by better communicating expectations and by providing resources for social, methodological, and pedagogical skills. More specific strategies are a) prerequisite courses that use quantitative measurements as the most significant causes of anxiety, b) educators to better state what a good practice of learning in their course is, c) mixing local and international students in courses i.e. groupwork or other class interactivity.